5C.01: LITTLE DIFFERENCE IN SALT INTAKE CRUCIALLY AFFECTS FUTURE BLOOD PRESSURE LEVELS IN THE GENERAL POPULATION. (June 2015) - Murai, S.; Takase, H.; Sugiura, T.; Yamashita, S.; Ohte, N.; Dohi, Y.
Abstract : Objective: A causal relationship between salt and hypertension has been argued for a long time. Epidemiological cross-sectional studies demonstrated higher incidence of hypertension in populations with higher dietary salt than in those with lower dietary salt and interventional studies investigated the effects of drastic changes in dietary salt in individuals. However, there is not sufficient evidence proving that individuals with relatively high salt intakes show an accelerated increase in blood pressure compared to those with a relatively low salt intakes over a long period of observation. Thus, the present observational study was designed to investigate whether individual levels of dietary salt affect future increases in blood pressure in the general population. Design and method: Individual salt intake was estimated by calculating 24-hour urinary salt excretion using a spot urine in normotensive 6, 249 participants in our physical check-up program (53.3 ± 11.4 year-old). After baseline examination, they were followed up for the median of 1, 089 days with the endpoint being the development of hypertension. Results: During the follow-up period, hypertension developed in 1, 027 participants (73.0 per 1, 000 person-years) with the incidence being more frequent in male than female participants. After adjustment for possible risk factors, the hazard ratio of incident hypertension in participants with salt intake higher than the target recommended by the Japanese Ministry of Health, Labour and Welfare (male, <9.0 g/day; female, <7.5 g/day) was 1.25 (95% confidence interval 1.04 to 1.50). In multivariate Cox hazards regression analysis, baseline salt intake and the yearly change in salt intake during the follow-up period (as continuous variables) correlated with the incidence of hypertension. Furthermore, both the yearly increase in salt intake and baseline salt intake showed significant correlations with the yearly increase in systolic blood pressure in multivariate regression analysis after adjustment for possible risk factors. Conclusions: Both relatively high levels of dietary salt intake at baseline as well as gradual increases in dietary salt during the follow-up period are associated with future increases in blood pressure and the incidence of hypertension in the general population.